MSMEs Marketing Strategy with the Use of Social-Media in the COVID-19 Pandemic Era - Kadar Nurjaman (International Journal of Science and Society, 2021)
Micro, Small, and Medium Enterprises, commonly abbreviated as MSMEs, is one of the pillars of the economy in Indonesia. It is proven that the MSMEs sector has repeatedly survived various crises that hit Indonesia starting from the monetary crisis in 1998 and the global crisis in 2008. Entering 2020, the world is again experiencing a more severe crisis, namely the COVID-19 pandemic. This crisis is seen as more severe because it has caused a worldwide health emergency that impacts other sectors, especially the economy. Restrictions on outdoor activities known as lockdowns have caused world economic activities to stop. This also impacts the activities of the MSMEs sector, which relies on economic turnover that comes from human activities. The MSMEs sector has been able to survive because of the direct marketing activities of individuals. The prohibition of gathering and opening a business openly (especially in the culinary sector) has had a significant impact on sustainability. Because of this, new marketing strategies for MSMEs sector players are needed to survive and even grow during the COVID-19 pandemic as it is today. Since the COVID-19 pandemic is imminent, this study aims to develop a marketing strategy for small businesses. This study employs a descriptive method and a qualitative approach. When the COVID-19 pandemic begins, UMPM must develop a marketing strategy that will allow them to continue to grow their business or at least to survive. There are eight reasons, namely a) Consumers are active on Social-Media; b) Easy contact with consumers; c) Increase Brand Visibility; d) The widest WOM container; e) e) Has Many Types of Platforms with Different Types of Consumers; f) Assisting in consumer targeting and retargeting; g) Using media more effectively, h) Increasing sales.